Rate of Productivity for Bore Pile Construction: A Case Study in Shah Alam - Syahrul Khalidi Bin Ab Rahman; Siti Khalijah Binti Yaman (Journal of Structural Monitoring and Built Environment, 2026)
This study investigates the productivity rate of bore pile construction at a site in Shah Alam, focusing on identifying factors influencing efficiency. Bore pile construction productivity is critical to project success, yet comprehensive data remains limited. This research measures production rates and analyzes factors such as equipment performance, worker efficiency, soil conditions, and weather. Utilizing site observation methods, data on bore pile depths ranging from 900 mm to 2000 mm was meticulously recorded. The analysis revealed variations in productivity rates based on pile size and identified bottlenecks in equipment availability and weather disruptions. These findings highlight the importance of effective equipment management, proactive construction planning, and optimized resource allocation to minimize delays and enhance operational efficiency. Overall, this study provides practical recommendations for improving bore pile construction productivity and serves as a valuable reference for contractors, project managers, and researchers in geotechnical engineering.